Keluarga Sebagai Lembaga Dakwah Pembentukan Karakter - Muhtar, Alvin Afif (Universitas Nahdlatul Ulama Blitar, 2023)
The family has a very important role in shaping children's character, especially in an Islamic perspective. The family as a da'wah institution in a small scope plays a role as a preacher who invites children to do ma'ruf and forbids munkar. Parents act as good role models for children, so that good values are not only theoretical but can be seen and felt by children. In Islam, character is also referred to as morals, which includes aspects of psychology, morals, or character that characterize a person. The family is the main and best place to train children's character intelligence, as well as prepare children's lives in society. In Islamic-based character education, the family has a very significant role in shaping children's character, especially through exemplary and habituation. Parents are expected to be good role models for children, so that good values can be applied in everyday life. In Islam, Islamic-based character education cannot be separated from faith and moral education, namely education about the basics of faith, religious beliefs, morality, praiseworthy morals and good character. Character education requires a long-term process that must begin early in life gradually and continuously.